2008
DOI: 10.1111/j.1365-2621.2008.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

A new vegetable oil from noni (Morinda citrifolia) seeds

Abstract: The nutritional quality and safety of oil extracted from noni (Morinda citrifolia) seeds was evaluated to determine its potential as a useful vegetable oil. The average oil content of noni seeds was found to be 124.9 g kg 1 . The mean linoleic acid content of crude noni seed oil was 59.4%. The average b-sitosterol, campesterol, stigmasterol, and a-tocopherol contents of noni seed oil were 4310, 2195, 2020, and 382 mg kg )1 , respectively. No evidence of acute oral toxicity was observed for noni seed or the oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 5 publications
0
17
1
2
Order By: Relevance
“…More recently, the fruit has been used to produce dietary supplements. French Polynesia has been a major source of this juice where noni fruit puree constitutes one of the area’s largest agricultural exports [ 12 ]. In fact, more than 21,000 metric tons of this puree was exported in the past decade [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the fruit has been used to produce dietary supplements. French Polynesia has been a major source of this juice where noni fruit puree constitutes one of the area’s largest agricultural exports [ 12 ]. In fact, more than 21,000 metric tons of this puree was exported in the past decade [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect may explain, at least in part, the inhibition of COX-2 enzymes by NSO. The possibility of the inhibitory activity being due to linoleic acid is supported by analyses published by West and colleagues [14] which showed that linoleic acid accounted for 89.9 ± 19.2 g/kg of dried noni seeds and 594.5 ± 60.5 g/kg of the crude seed oil. These quantities make NSO a rich source of linoleic acid.…”
Section: Discussionmentioning
confidence: 88%
“…This finding suggests that NSO has little or no potential for clogging up pores of the skin when used as a cosmetic ingredient. Analyses by West and colleagues [14] showed that NSO contains linoleic and oleic acids, which are considered healthy fatty acids. In fact, oleic fatty acid can be used in cooking of foods [26][27][28] and for formulations of various cosmetics [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the fruit is used to produce a juice that is often consumed to improve overall health. A major source of this juice is French Polynesia where noni fruit puree constitutes one of the largest agricultural exports [12]. In fact, more than 21,000 metric tons of this puree was exported in the past decade [13].…”
Section: Introductionmentioning
confidence: 99%